Occurrence of a nonsulfated chondroitin proteoglycan in the dried saliva of Collocalia swiftlets (edible bird's-nest) - Hiroki Nakagawa (2018)
Despite their wide occurrence, proteoglycans (PGs) have never been isolated from the saliva of higher animals. We found that the Collocalia glycoproteins isolated from edible birds'-nests (the dried forms of regurgitated saliva of male Collocalia swiftlets) were rich in a PG containing nonsulfated chondroitin glycosaminoglycans (GAGs). We have devised a method to isolate a PG from the water extract of the white nest built by Aerodramus fuciphagus (white nest swiftlets) with a yield of 2-mg PG per gram nest. This PG contained 83% of carbohydrates, of which 79% were GalNAc and GlcUA (D-glucuronic acid) in an equimolar ratio. By using chondroitin AC lyase, the structure of GAGs in this PG was established to be chondroitin (→ 4GlcUAβ1 → 3GalNAcβ1 →)nchains. The average molecular mass of the chondroitin chain was estimated to be 49 kDa by gel filtration. We have isolated a linkage region hexasaccharide, ΔHexUAα1 → 3GalNAcβ1 → 4GlcUAβ1 → 3Galβ1 → 3Galβ1 → 4Xyl, from this PG by chondroitinase ABC digestion to show that the GAGs in this PG are also linked to the core protein through the common tetrasaccharide linker, GlcUAβ1 → 3Galβ1 → 3Galβ1 → 4Xyl, found in various PGs. As water was not effective in extracting uronic acid-containing glycoconjugates from the black nest built by black nest swiftlets (A. maximus), we used 4 M guanidium chloride and anion-exchange chromatography in the presence of urea to extract and isolate about 30 mg of a chondroitin PG preparation from 10 g of the desialylated black nest. As the biological significance of chondroitin is still not well understood, bird's nest should become a convenient source for preparing this unique GAG to study its biological functions. © 2007 Oxford University Press.